2018
DOI: 10.5937/ffr1801037t
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial activity of essential oils against Listeria monocytogenes

Abstract: Food poisoning caused by Listeria monocytogenes leads to a 30% rate of mortality among patients. The application of essential oils (EOs) to food products is a suitable strategy to control pathogens and to extend their shelf life by reducing microbial levels. The objective of this study was to evaluate the antimicrobial potential of essential oils (EOs) against L. monocytogenes. The EOs used in this study were caraway (Carum carvi), cinnamon (Cinnamomum zeylanicum), dill (Anethum graveolens), clove (Syzygium ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“…The low e ciency is probably due to the losses of volatile compounds of essential oil during storage and/or extraction as it has been observed. The antibacterial activity of several plants against this strain has been studied by (Tomičić et al 2018), where it was found that cinnamon essential oil exhibited the highest activity. Almost the same results of the antibacterial activity of essential oils extracted from C. sinensis peel against Pseudomonas aeruginosa and Staphylococcus aureus were obtained by Edogbanya et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…The low e ciency is probably due to the losses of volatile compounds of essential oil during storage and/or extraction as it has been observed. The antibacterial activity of several plants against this strain has been studied by (Tomičić et al 2018), where it was found that cinnamon essential oil exhibited the highest activity. Almost the same results of the antibacterial activity of essential oils extracted from C. sinensis peel against Pseudomonas aeruginosa and Staphylococcus aureus were obtained by Edogbanya et al (2019).…”
Section: Discussionmentioning
confidence: 99%
“…All isolates were susceptible to antibiotic classes of fluoroquinolone, carbapenem, and glycylcycline regardless of the types of chickens (Table 4). Salmonella has the capability to adapt to undesirable external environment conditions and it can develop mechanisms to overcome the burden given by the external environment such as antimicrobial drugs (Tomičić et al, 2018). This process is known as antimicrobial resistance.…”
Section: Prevalence Of Antimicrobial Resistance Salmonellamentioning
confidence: 99%
“…The results obtained after qualitative evaluation of antibacterial activity of CST, CST-TTO and CST-CO cues against Staphylococcus aureus, Bacillus subtilis, Escherichia coli, and Salmonella typhimuriumare summarized in The, 2000; Emiroğlu et al, 2010;Gómez-Estaca et al, 2010;Moreno, Scheyer, Romano, & Vojnov, 2006;Tomičić, Čabarkapa, Varga, & Tomičić, 2018).…”
Section: Antibacterial Activity: Qualitative Evaluationmentioning
confidence: 99%